Pré-tratamento de biomassa microalgácea utilizando enzimas hidrolíticas provenientes de isolados fúngicos - Curti, Cristina (2019)
In the biogas production process,using microalgae biomass, the main challenge is the pretreatment stage, specifically the hydrolysis of the cell wall. Degradation of organic matter can be accomplished by enzymes produced by various microorganisms, especially filamentous fungi. Among the existing pretreatment processes, biological was chosen as the most economically advantageous and ecological-friendly method, although it is directly depends on hydrolysistime. The objective of this work was to evaluate the hydrolysis processes of microalgae biomass using fungi producing hydrolytic enzymes. Twenty-one filamentous fungi were isolated and the cell extractive potential of cellulose, lipase, pectinase and protease were evaluated. The 4 ones with higher activity were used to hydrolyze microalgaebiomass referenced to Chlorellasp., thatgrown in controlled environment, and consortium biomass derived from anaerobic effluent.The treatmentof the microalgae biomass referenced, the fungus Trichodermasp. with proteinase activity, solubilized 85.33% of organic matter for 48 h with 20% of enzymatic extract. In relation to the biomassderivated by sludge treatment, the protease activity obtained 54.33% of DQOsusing the fungus Trichodermasp. with 20% crude enzymatic extract at end of 48 htest. In summary, the microalgae biomass referenced was hydrolyzed 66% more than the mixotrophic biomassevaluating the DQO solubilized. The results showed that the enzymes produced by the isolated fungi have high biomass solubilization capacities. Biological pre-treatment has a great potencial of application in the production of biogas, after the analysis of theresults it was possible to conclude that the choice of the enzymatic activity and the concentration of the fungal extracts can be used as keys to reduce the main disadvantage of the biological treatments, the hydrolysis time.